The Status of Women in Islam: Surat Al-Nisaa as a Model - Al Hessa, Immad Saliman Awad (Dirasat: Shari’a and Law Sciences, 2020)
This study aims to explain the rights imposed by Islam on women, through Surah An-Nisa, because the Surah dealt with many pre-Islamic customs, which wronged women, as women were deprived of their right to friendship, so Islam obliged their guardian to give it to her, and husbands were obliged to fulfill it. The study adopted the inductive method and the analytical method by explaining the reason for the naming and discussing the claim of discrepancy in its topics and the statement of the rights required by the Surah for women, including material rights and moral rights. The study pointed out some of the rights in which Jahiliyyah has wronged women, and Surah An-Nisa mentioned a woman’s right to inheritance, her right to own property, and detailed her right to live a decent and secure life, so the study came to show the virtue of Islam over women and explains how Jahiliyyah has wronged her and warns of many customs, in which some people return to the act of Jahiliyyah. The study recommended that the topic of women be given more research and study and the need to circulate studies on the fairness of Islam for women to ministries and official departments, especially the Ministry of education; to create a state of awareness of women’s rights.